HARQ Implementation for Efficient MAC to MAC Video Streaming over Mobile WiMAX (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
IEEE 802.16e is the standard for Mobile WiMAX which was introduced by the IEEE committee to provide broadband access in rural and urban areas over fixed wireless channels. Mobile WiMAX is an enhanced version of IEEE 802.16 standard with mobility support. There are lots of challenges involved in the service provided by the Mobile WiMAX. Efficient data transfer between different layers of mobile WiMAX is one of the major research issues. In this work HARQ (Hybrid Automatic Repeat Request) technique is implemented in Qualnet environment for an efficient transmission of video streaming across PHY(Physical) and MAC(Medium Access Control) layer of mobile WiMAX (Worldwide Interoperability for Microwave Access). HARQ utilizes both FEC (Forward Error Correction) an d ARQ (Automatic Repeat Request) techniques to reduce the delay, jitter and to increase throughput efficiently under prescribed quality of service constraint. Different Scheduling schemes and cross layer approaches that support mobile WiMAX are analysed. mmSIR scheduler is used in this work since it allocates resources priority wise. Diffferent network quality parameters like end to end delay,average jitter,and average throughput have been analysed by using existing ARQ and implemented HARQ techniques.Both ARQ and HARQ techniques are compared for a video application.